Overview of the Accuracy of Fracture Main Diagnostic Codes in Inpatients at Gatot Soebroto Army Hospital - Carono; Siswati; Deasy Rosmala Dewi; Laela Indawati (Open Access Indonesian Journal of Medical Reviews, 2022)
Coding activities include the coding of diagnosis and the coding of medical treatment. The important thing that must be considered by medical recorders is the accuracy in giving the diagnosis code. This study aims to determine the accuracy of the main diagnostic code for fractures in inpatients at Gatot Soebroto Army Hospital using ICD-10. This research is an observational study with a descriptive method. The study was conducted at the medical record unit of the Gatot Soebroto Army Central Hospital from October to December 2020. Sampling in this study was carried out using a systematic random sampling technique. The sample in this study was the medical record of patients with a fracture diagnosis at Gatot Soebroto Army Hospital. This study found that standard operating procedures (SOPs) for giving diagnosis codes in general according to ICD-10 at Gatot Soebroto Army Hospital already exist. However, the SOP code for fracture diagnosis is not yet available. Most of the documents (72.88%) had a diagnosis code that did not match the ICD-10. In conclusion, Gatot Soebroto Army Hospital does not yet have a special SOP regarding the diagnosis code for fracture cases. Most fracture diagnosis codes in medical record documents are incorrect. This is probably due to the lack of accuracy of the coder in coding the diagnosis, the absence of an evaluation or audit of the diagnosis coding for fracture cases, and the writing of the diagnosis by doctors being unclear and illegible.